Global collective action - Sandler, Todd (Cambridge University Press, 2004)
This book examines how nations and other key participants in the global community address problems requiring collective action. The global community has achieved some successes, such as eradicating smallpox, but other efforts to coordinate nations' actions, such as the reduction of drug trafficking, have not been sufficient. This book identifies the factors that promote or inhibit successful collective action at the regional and global level for an ever-growing set of challenges stemming from augmented cross-border flows associated with globalization. Modern principles of collective action are identified and applied to a host of global challenges, including promoting global health, providing foreign assistance, controlling rogue nations, limiting transnational terrorism, and intervening in civil wars. Because many of these concerns involve strategic interactions where choices and consequences are dependent on one's own and others' actions, the book relies, in places, on elementary game theory that is fully introduced for the uninitiated reader.